Investigating Cracks Prevention in Concrete Utilizing the Self-Healing Concept of Bacillus Subtilis Bacteria - Masaud Ahmad Khan; Hamayun Khan; Muhammad Haris Javed; Zohaib Ullah; Atif Mehmood Khan; Khuda Bukhsh (Journal of ICT, Design, Engineering and Technological Science, 2021)
Concrete is the most common and widely used construction material. In the concrete structure, cracks are sometimes produced due to external loads and other reasons. Due to cracks, the concrete begins to take compression loads in the structure; therefore, repairing such cracks is essential. Different methods are used to repair the cracks in concrete, but in this thesis, we are working on bacteria base self-healing of cracks in concrete. For self-healing concrete different types of bacteria are used but we are using the bacteria named Bacillus subtilis in concrete. By adding bacillus subtilis and calcium lactate we find that the concrete becomes more strengthened and self-healed as compared to normal concrete. There are two methods of adding the bacteria to concrete which is direct adding an encapsulation method. We followed the direct application method in this method the bacteria is added directly to concrete. The test results show that the bacterial concrete has higher compression strength and self-healing concrete.